The Social Essence Of An Innovative Pedagogical Approach - Bakhtiyor Kayumov; Navbahor Abdulhakimova (International Scientific and Current Research Conferences, 2020)
The article provides the social essence of an innovative pedagogical approach. A dialectical connection between the past and the present, as well as the development of the future, and this connection reflected in the education system, in its content, in production is shown here.